2018
DOI: 10.1038/s41419-018-0706-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Aberrant mannosylation profile and FTX/miR-342/ALG3-axis contribute to development of drug resistance in acute myeloid leukemia

Abstract: Drug-resistance is a major problem in acute myeloid leukemia (AML) chemotherapy. Aberrant changes in specific N-glycans have been observed in leukemia multidrug resistance (MDR). MicroRNAs (miRNAs) and long non coding RNAs (lncRNAs) act as key players in the development of AML resistance to chemotherapy. In the present study, the N-glycan profiles of membrane proteins were analyzed from adriamycin (ADR)-resistant U937/ADR cells and sensitive line U937 cells using mass spectrometry (MS). The composition profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…In accord with Zhang et al's study, its expression was abnormally upregulated following doxorubicin-based chemotherapy and knockdown of UCA1 helped overcome chemoresistance in pediatric AML by suppressing glycolysis via binding miR-125a [189]. FTX is another lncRNA involved in chemoresistance, and it controlled the expression of ALG3 by binding miR-342 [193]. HOXA cluster antisense RNA 2 (HOXA-AS2) was significantly upregulated in BM samples from AML patients after treatment with adriamycin-based chemotherapy and sponged miR-520c-3p to contribute to chemoresistance in AML [195].…”
Section: Prognostic Value Of Lncrnas In Acute Myeloid Leukemiasupporting
confidence: 65%
See 1 more Smart Citation
“…In accord with Zhang et al's study, its expression was abnormally upregulated following doxorubicin-based chemotherapy and knockdown of UCA1 helped overcome chemoresistance in pediatric AML by suppressing glycolysis via binding miR-125a [189]. FTX is another lncRNA involved in chemoresistance, and it controlled the expression of ALG3 by binding miR-342 [193]. HOXA cluster antisense RNA 2 (HOXA-AS2) was significantly upregulated in BM samples from AML patients after treatment with adriamycin-based chemotherapy and sponged miR-520c-3p to contribute to chemoresistance in AML [195].…”
Section: Prognostic Value Of Lncrnas In Acute Myeloid Leukemiasupporting
confidence: 65%
“…An oncogenic activity of lncRNA was also shown by HOTAIR that regulating the expression of c-Kit in AML cells through competitively binding miR-193a, an important tumor-suppressor miRNA to predict a poor clinical outcome [190]. HOTAIRM1, a lncRNA located in the HOXA genomic region, is related to myeloid differentiation which sequestered miR-20a, miR-106b and ↑in AML cell lines and CN-AML with biallelic CEBPA p27kip1 Role in promoting cells proliferation is to sequester hnRNP I to inhibit the expression of the cell cycle regulator p27kip1 [167] ↑in HL-60 and HL-60/ADR miR-125a Poor chemotherapy overcome [189] HOTAIR ↑in de novo AML patients miR-193a;c-Kit Increase AML cells proliferation, inhibited apoptosis and infiltration of leukemic blasts and number of AML cells colony formation, and shorten overall survival time [190] ↑in LSC p15 Promote the self-renewal of leukemia stem cells [191] CCAT1 ↑in HL60 and AML PB miR-155, c-Myc Upregulated c-Myc expression to increased cells proliferation and differentiation by its competing endogenous RNA (ceRNA) activity on miR-155 [192] FTX ↑in U937 and THP-1 miR-342, ALG3 Drug resistance [193] PANDAR ↑ANDARLINK Predict adverse prognosis in AML [181] HOXA-AS2 ↑in APL TRAIL-mediated pathway Lead to fine-tuning of apoptosis during ATRA-induced myeloid differentiation [194] ↑00PERLINK \l "_ENREF_200" \o "Zhao H, 2013 #197" or><adriamycin-based chemotherapy and in U/A and T/A cells miR-520c-3p/ S100A4 Axis Knockdown of lncRNA HOXA-AS2 inhibited ADR cell proliferation and chemoresistance of AML by the miR-520c-3p/ S100A4 Axis, and promoted apoptosis [195] HOTAIRM1 is an oncogenic lncRNA that upregulated c-Myc via its ceRNA activity on miR-155 to repress monocytic differentiation and promote cell growth [192]. The host non-coding transcript of miR-223 of linc-223, found downregulated in AML, is a functional lncRNA which regulated proliferation and differentiation of AML cells by binding miR-125-5p [203].…”
Section: Prognostic Value Of Lncrnas In Acute Myeloid Leukemiamentioning
confidence: 99%
“…Recently and in line with this, ALG3 was also detected in cellular compartments apart from the ER, albeit the function of this protein in the cytosol and nucleus remains unclear (Hacker, Schultheiss, & Kurzik‐Dumke, ; Hacker, Schultheiss, Doring, & Kurzik‐Dumke, ). Furthermore, ALG3 seems to be associated with cervical cancer (Yang et al, ) and was also found to affect drug‐resistance in acute myeloid leukemia cells (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that FTX could compete with miR‐374a to inhibit epithelial‐mesenchymal transition (EMT) of hepatocellular carcinoma (HCC) cells or inhibit their proliferation by binding to an E3 ligase MDM2 . Another study reported that FTX could activate ALG3 expression by eliminating interference of miR‐342 in acute myeloid leukaemia (AML) . However, whether lncRNA FTX participates in lung cancer progression and the possibility for FTX to act as a prognostic marker remain unclear.…”
Section: Introductionmentioning
confidence: 99%